2013
DOI: 10.1167/iovs.12-10742
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Defocus-Induced Myopia in Chickens

Abstract: Citation: Woods J, Guthrie SE, Keir N, et al. Inhibition of defocus-induced myopia in chickens. Invest Ophthalmol Vis Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Recent animal studies 45,46 further indicated that lens-induced relative myopic defocus of the peripheral retina could significantly reduce the developmental rate of lens-induced myopia in chickens. Based on the results from animal experiments, numerous clinical trials have attempted to impose relative myopic defocus on the peripheral retina via different optical designs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal studies 45,46 further indicated that lens-induced relative myopic defocus of the peripheral retina could significantly reduce the developmental rate of lens-induced myopia in chickens. Based on the results from animal experiments, numerous clinical trials have attempted to impose relative myopic defocus on the peripheral retina via different optical designs.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, there is much interest in the different patterns of peripheral refraction found in hyperopic and myopic eyes. In particular, because imposed defocus in the periphery can alter central refractive development in animals, 16, 3436 it has been speculated that the pattern of peripheral refraction could influence central refractive development. 2 Specifically, it is possible that relative peripheral hyperopia typically exhibited by myopic eyes (at least in the horizontal meridian) 32, 37 could serve as a stimulus for myopia progression.…”
Section: Discussionmentioning
confidence: 99%
“…Bifocal lenses can induce refractions that differ from those imposed centrally but are inconsistent with a strictly peripheral influence . Some results are consistent with increased depth of focus or spherical aberration reducing the signal to the direction of defocus centrally without producing form deprivation myopia …”
Section: Counterpointmentioning
confidence: 99%